Trends and Disparities in Liver Transplantation in the United States: A Nationwide Analysis of Demographic, Clinical, and Socioeconomic Factors (2016–2021) - Vignesh Krishnan Nagesh; Vivek Joseph Varughese; Marina Basta; Emelyn Martinez; Shruthi Badam; Lokaesh Subramani Shobana; Abdifitah Mohamed; Alin J; Simcha Weissman; Adam Atoot (Medical Sciences, 2025)
Background: Liver transplantation has become the standard of care for patients with end-stage liver disease. Despite advances in surgical techniques, immunosuppression, and perioperative care, disparities in access and outcomes persist across demographic and socioeconomic lines. Objective: To assess trends and disparities in liver transplant admissions in the United States from 2016 to 2021, examining demographic patterns, in-hospital mortality, hospital charges, length of stay, and socioeconomic factors. Methods: Using the National Inpatient Sample (NIS) from 2016 to 2021, we identified liver transplant admissions using ICD-10 PCS codes 0FY00Z1 and 0FY00Z2. Demographic characteristics (age, sex, race, insurance status, and income quartile), clinical outcomes, and resource utilization metrics were analyzed. One-way ANOVA and Hensel’s test were used to assess variance and distribution homogeneity, with a significance threshold of p < 0.05. Results: A total of 9677 liver transplant admissions were analyzed. The mean recipient age remained stable (51–52 years), with males comprising ~62% of transplants. White patients constituted the largest group of recipients (~66–68%), followed by Hispanic (~14–17%) and Black patients (~7–10%). The proportion of transplants relative to liver failure admissions remained stable across racial groups, indicating no widening racial gap during the study period. In-hospital mortality post-transplant remained low (2.37–3.52%) and did not differ significantly by race (p = 0.23), sex (p = 0.24), or income quartile (p = 0.13). Similarly, Charlson Comorbidity Index > 5 did not predict inpatient mortality (p = 0.154). Hospital charges ranged from $578,000 to $766,000, with an average stay of ~21 days. Conclusions: Liver transplantation outcomes, including in-hospital mortality, appear consistent across demographic and socioeconomic groups once patients are admitted for transplant. However, broader disparities in access persist, necessitating further research into pre-transplant barriers and long-term outcomes. These findings support the need for equitable healthcare strategies aimed at optimizing transplant candidacy and survival across all populations.